Conduction Mechanism of Chitosan/Methylcellulose/1-Butyl-3 Methyl Imidazolium Bis (Trifluoromethylsulfonyl) Imide (BMIMTFSI) Biopolymer Electrolyte Doped with Ammonium Triflate - M.S.M.Misenan; A.S.A. Khiar (Institut Kimia Malaysia, 2024)
Vol 22 No 4